Sự ảnh hưởng của kiến thức tài chính đến đòn bẩy tài chính và hiệu quả đầu tư - Phùng Thái Minh, Trang; Phạm Ngọc Tường, Loan; Nguyễn Đăng, Lâm (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
Financial literacy largely contributes to economic and social wellbeing. However, the research on the effect of financial literacy on the use of financial leverage and investment performance has not been clearly examined. Based on the survey data on 400 individual investors, approaches to test hypotheses are multiple linear regression and structural equation models. The results show that financial literacy directly and indirectly affects the use of financial leverage and investment performance. Income and experience also have an indirect effect on investment performance. The results imply the important role of financial literacy in using financial leverage effectively and achieving desired investment results.
Keywords: Financial literacy; Investment experience; Investment performance; Use of financial leverage; Income